Physicochemical and Sensory Characteristics of Kecombrang (Etlingera elatior) Flower Leather (The Study of Type and Concentration of Hydrocolloids Treatment) - Nugroho, Satrio Ari; Rosida Rosida; Rahmawati Rahmawati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Flower leather is a processed food product made primarily from flowers as the main ingredient. It is a thin, sheet-like product with a distinctive consistency and taste, depending on the type of raw material used. The addition of various types of hydrocolloids is carried out to improve the texture of flower leather. Other ingredients used include granulated sugar and citric acid. The method used was a Completely Randomized Design (CRD) with a factorial pattern, where Factor I was the type of hydrocolloid (carrageenan, gum arabic, and CMC), and Factor II was the hydrocolloid concentration (0.3%, 0.6%, 0.9%). The obtained data were analyzed using ANOVA, followed by the DMRT post hoc test at a 5% significance level. The results showed a significant interaction (p<0.05). Flower leather with the addition of carrageenan at a concentration of 0.9% is the best treatment with the characteristics of water content 7.99%, water activity 0.5, yield 27.05%, pH 4.84, crude fiber content 2.32%, and tensile strength 2.781 N. The resulting of organoleptic properties, including color, aroma, taste, texture, and overall preference, were rated at 4.2 (like), 3.4 (somewhat like), 3.08 (somewhat like), 3.44 (somewhat like), and 3.28 (somewhat like).